A Framework for Policy Crowdsourcing - Prpić, John (Institutional Knowledge at Singapore Management University, 2014)
What is the state of the literature in respect to Crowdsourcing for policy making? This work attempts to answer this question by collecting, categorizing, and situating the extant research investigating Crowdsourcing for policy, within the broader Crowdsourcing literature. To do so, the work first extends the Crowdsourcing literature by introducing, defining, explaining, and using seven universal characteristics of all general Crowdsourcing techniques, to vividly draw-out the relative trade-offs of each mode of Crowdsourcing. From this beginning, the work systematically and explicitly weds the three types of Crowdsourcing to the stages of the Policy cycle as a method of situating the extant literature spanning both domains. Thereafter, we discuss the trends, highlighting the research gaps, and outline the overlaps in the research on Crowdsourcing for policy, stemming from our analysis.